2011
DOI: 10.1088/0031-9155/56/17/001
|View full text |Cite
|
Sign up to set email alerts
|

Treatment precision of image-guided liver SBRT using implanted fiducial markers depends on marker–tumour distance

Abstract: The purpose of this study is to assess the accuracy of day-to-day predictions of liver tumour position using implanted gold markers as surrogates and to compare the method with alternative set-up strategies, i.e. no correction, vertebrae and 3D diaphragm-based set-up. Twenty patients undergoing stereotactic body radiation therapy (SBRT) with abdominal compression for primary or metastatic liver cancer were analysed. We determined the day-to-day correlation between gold marker and tumour positions in contrast-e… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

4
103
1

Year Published

2017
2017
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 97 publications
(108 citation statements)
references
References 32 publications
4
103
1
Order By: Relevance
“…Many studies on liver motion characterization using markers have been published. 12,16,19 Seppenwoolde et al showed that the tumor position can be accurately predicted using implanted markers considering that there is a real influence of the marker-tumor distance on the set-up accuracy. They also showed that the diaphragm dome was the second best predictor of tumor motion and that it could be used as a surrogate for tumor located close to it.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies on liver motion characterization using markers have been published. 12,16,19 Seppenwoolde et al showed that the tumor position can be accurately predicted using implanted markers considering that there is a real influence of the marker-tumor distance on the set-up accuracy. They also showed that the diaphragm dome was the second best predictor of tumor motion and that it could be used as a surrogate for tumor located close to it.…”
Section: Discussionmentioning
confidence: 99%
“…They also showed that the diaphragm dome was the second best predictor of tumor motion and that it could be used as a surrogate for tumor located close to it. 19 Park et al studied the liver motion characteristics based on fiducial markers tracked with the X-rays projections of the CBCT scans. Their results showed large variations in liver motion and their conclusion was similar to those of Seppenwoolde et al, mainly that the distance between the markers and the tumor was a major element to track.…”
Section: Discussionmentioning
confidence: 99%
“…All patients were implanted with 2–4 fiducials near the tumor under CT guidance 11. Simulation was typically administered 7–10 days after the implantation, which can minimize the risk of marker migration.…”
Section: Methodsmentioning
confidence: 99%
“…Initially the motion was measured with video fluoroscopy registrations and later on with a reconstruction of 4DCT registrations. 14,15 No margin between gross target volume and clinical target volume was used. Planning target volume (PTV) margins were initially based on the Karolinska experience.…”
Section: Treatment Preparation and Deliverymentioning
confidence: 99%
“…tracking or non-tracking), the amplitude of the respiratory-induced motion, and the distance between the center-off-mass of the marker configuration and the center of the tumor. 15 For conventional linac based treatments the personalized margins that were applied clinically ranged between 8-10 mm superior-inferior, and 5-7 mm left-right and anterior-posterior. For CyberKnife treatments the personalized margins ranged between 5 and 7 mm in all directions.…”
Section: Treatment Preparation and Deliverymentioning
confidence: 99%